Cardiomyocyte Inflammasome Signaling in Cardiomyopathies and Atrial Fibrillation: Mechanisms and Potential Therapeutic Implications - Chen, Gong; Chelu, Mihail G.; Dobrev, Dobromir; Li, Na (Frontiers in Physiology, 2018)
Inflammasomes are high molecular weight protein complexes in the cytosol of immune and other cells that play a critical role in the innate immune system in response to cellular stress. NLRP3 inflammasome, the best-understood inflammasome, is known to mediate the maturation (activation) of caspase-1 from pro-caspase-1, causing the maturation and release of cytokines (e.g., interleukin-1β) and potentially leading to a form of inflammatory programmed cell death called pyroptosis. Previous work has shown that the NLRP3 components are expressed in cardiomyocytes and cardiac fibroblasts and recent studies have identified the NLRP3 inflammasome as a key nodal point in the pathogenesis of cardiomyopathies and atrial fibrillation, which may create an opportunity for the development of new therapeutic agents. Here we review the recent evidence for a role of NLRP3 inflammasome in the cardiomyocytes and discuss its potential role in the evolution of cardiac remodeling and arrhythmias and new opportunities created by these very recent developments.